Giant Hypennarket is one of main player in consumer good retailing industry in Indonesia. Changing environtment and increasing competition pressure have put the finn in a need of marketing strategy adjustment in order to retain the existing and to gain new market segments. This study presented steps taken in developming a new marketing strategy plan based on study of consume(s preference and enterprise perfonnace analysiS. A new marketing mix, has been developed based on consumer preference and - Suharno .; Ika Sulistiya (Buletin Ekonomi Perikanan, 2008)
Giant Hypennarket is one of main player in consumer good retailing industry in Indonesia. Changing environtment and increasing competition pressure have put the finn in a need of marketing strategy adjustment in order to retain the existing and to gain new market segments. This study presented steps taken in developming a new marketing strategy plan based on study of consume(s preference and enterprise perfonnace analysiS. A new marketing mix, has been developed based on consumer preference and enterprise perfonnance studies. The study has been focused on sea food and fish products of the retailer. Objectives of the studies are to Identify dominant marketing variables of the finn that best meet consumer preferences and to fonnulate new or adjusted marketing mix that best fits the business environment and Challenges. The development of new marketing mix began by conducting consumer preference study in whichconsumers are requested to expresses their impression and evaluation on existing Giant marketing strategy. In the same manner, intemal officers of Giant hypennarket having direct responsibility in marketing have been asked to give their self evaluation on their own marketing strategy. In both studies, elements of Giant marketing mix, the so called 7 P's, were. evaluated. Empirical data has been drawn by using survey and interview techniques. Sample respondents representing consumers have been selected by applying purposive sampling methods. Questionnaires were developed to catch consumer preferences, consumer evaluation and suggestions on the existing marketing mix. The data has then been analyzed by applying descriptive statistics methods. Seven marketing variables of Giant Hypennarket being analyzed are product mix, price mix, place mix, promotion mix, process mix, people mix and physical evidence. These variables have been evaluated by both intemal management and consumers. New marketing mix is then developed based ~n the outcome of the analysis. It is indicated that Giant Hypermarket has applied the 7 Ps of the marketing mix adequately consistent. Four of the seven variables (product, price, promotion, people, and physical evidence) have been deemed appropriate, while the others have been deemed good. However, one element of promotion mix, namely public relation have been deemed poor by consumes. Evaluation by intemal management of the firm has put marketing variables to be significant factors for the success of the retailer. The analysis has revealed that two marketing variables, product mix and promotin mix are relatively more important than the others; Cosequently, these variables need to be put in priority in the firm marketing program. It is recommended, that (1) as a part product mix, the firm to put more care in sorting process to ensure quality, to intensify physical check up on the products, to use appropriate packing materials and to make up packing design. (2) In promotion mix, Giant Hypermarket is suggested to keep using and diversify the existing media to increase publication. In particular, the firm is suggested to increase the frequencies of sales promotion and public relation.